Use of a vascular sheath for introduction of radiofrequency ablation probe during radiofrequency ablation of osteoid osteoma - Munawwar Ahmed; Shyamkumar N Keshava; Vinu Moses; Suraj Mammen; Korula Mani Jacob; Vrisha Madhuri (Indian Journal of Radiology and Imaging, 2015)
Radiofrequency ablation (RFA) has now become a preferred treatment option for osteoid osteoma. Accurate placement of RFA probe into the nidus of osteoid osteoma is important for good clinical outcome. Various methods and techniques have been described in the literature available. We describe the technique of using a vascular access sheath for introduction of RFA probe after bone drilling, which prevents loss of access to drill track and also serves as a pathway for accurate placement of RFA probe, thereby reducing the risk of damage to the RFA probe tip itself and the surrounding soft tissue.